Isolation of Pseudomonas aromaticivorans sp. nov from a hydrocarbon-contaminated groundwater capable of degrading benzene-, toluene-, m- and p-xylene under microaerobic conditions - Banerjee, Sinchan; Bedics, Anna; Tóth, Erika; Kriszt, Balázs; Soares, André R.; Bóka, Károly; Táncsics, András (Frontiers in Microbiology, 2022)
Members of the genus Pseudomonas are known to be widespread in hydrocarbon contaminated environments because of their remarkable ability to degrade a variety of petroleum hydrocarbons, including BTEX (benzene, toluene, ethylbenzene and xylene) compounds. During an enrichment investigation which aimed to study microaerobic xylene degradation in a legacy petroleum hydrocarbon-contaminated groundwater, a novel Gram-stain-negative, aerobic, motile and rod-shaped bacterial strain, designated as MAP12ᵀ was isolated. It was capable of degrading benzene, toluene, meta- and para- xylene effectively under both aerobic and microaerobic conditions. The 16S rRNA gene sequence analysis revealed that strain MAP12ᵀ belongs to the genus Pseudomonas, with the highest 16S rRNA gene similarity to Pseudomonas linyingensis LYBRD3-7T (98.42%), followed by Pseudomonas sagittaria JCM 18195T (98.29%) and Pseudomonas alcaliphila JCM 10630T (98.08%). Phylogenomic tree constructed using a concatenated alignment of 92 core genes indicated that strain MAP12ᵀ is distinct from any known Pseudomonas species. The draft genome sequence of strain MAP12ᵀ is 4.36 Mb long, and the G+C content of MAP12ᵀ genome is 65.8%. Orthologous average nucleotide identity (OrthoANI) and digital DNA–DNA hybridisation (dDDH) analyses confirmed that strain MAP12ᵀ is distinctly separated from its closest neighbours (OrthoANI <89 %; dDDH <36%). Though several members of the genus Pseudomonas are well known for their aerobic BTEX degradation capability, this is the first report of a novel Pseudomonas species capable of degrading xylene under microaerobic conditions. By applying genome-resolved metagenomics, we were able to partially reconstruct the genome of strain MAP12T from metagenomics sequence data and showed that strain MAP12T was an abundant member of the xylene-degrading bacterial community under microaerobic conditions. Strain MAP12ᵀ contains ubiquinone 9 (Q9) as the major respiratory quinone and diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine as major polar lipids. The major cellular fatty acids of strain MAP12ᵀ are summed feature 3 (C16:1ω6c and/or C16:1ω7c), C16:0 and summed feature 8 (C18:1ω6c and/or C18:1ω7c). The results of this polyphasic study support that strain MAP12ᵀ represents a novel species of the genus Pseudomonas, hence the name of Pseudomonas aromaticivorans sp. nov. is proposed for this strain considering its aromatic hydrocarbon degradation capability. The type strain is MAP12ᵀ (=LMG 32466, =NCAIM B.02668 ).